2019
DOI: 10.1128/mcb.00148-19
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 5 Inhibits Glutamate-Induced Neuronal Cell Death through the Regulation of Calcineurin-Dependent Mitochondrial Dynamics in HT22 Cells

Abstract: Glutamate is an essential neurotransmitter in the central nervous system (CNS). However, high glutamate concentrations can lead to neurodegenerative diseases. A hallmark of glutamate toxicity is high levels of reactive oxygen species (ROS), which can trigger Ca2+ influx and dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Peroxiredoxin 5 (Prx5) is a well-known cysteine-dependent peroxidase enzyme. However, the precise effects of Prx5 on glutamate toxicity are still unclear. In this study, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…As shown in Figure 1(B), glutamate increased HyPer-Cyto and HyPer-Mito fluorescence to similar levels for up to 9 h after treatment. However, HyPer-Mito showed a dramatic increase compared to HyPer-Cyto at 12 h. In a previous study, we confirmed that glutamate treatment increased the expression level of Prx5 in a time-/ concentration-dependent manner and that glutamate-induced ROS generation was related to the upregulation of Prx5 expression [13]. The present study showed that co-treatment with N-acetyl-L-cysteine (an intensive ROS scavenger) or MitoTEMPO (a mitochondrial ROS scavenger) downregulated Prx5 expression, indicating that the upregulation of Prx5 was related to glutamate-induced ROS generation (Figure 1(C)).…”
Section: Glutamate Upregulated the Expression Level Of Cytprx5 And Mtsupporting
confidence: 81%
See 2 more Smart Citations
“…As shown in Figure 1(B), glutamate increased HyPer-Cyto and HyPer-Mito fluorescence to similar levels for up to 9 h after treatment. However, HyPer-Mito showed a dramatic increase compared to HyPer-Cyto at 12 h. In a previous study, we confirmed that glutamate treatment increased the expression level of Prx5 in a time-/ concentration-dependent manner and that glutamate-induced ROS generation was related to the upregulation of Prx5 expression [13]. The present study showed that co-treatment with N-acetyl-L-cysteine (an intensive ROS scavenger) or MitoTEMPO (a mitochondrial ROS scavenger) downregulated Prx5 expression, indicating that the upregulation of Prx5 was related to glutamate-induced ROS generation (Figure 1(C)).…”
Section: Glutamate Upregulated the Expression Level Of Cytprx5 And Mtsupporting
confidence: 81%
“…Of the six Prx subtypes, the antioxidant effect of Prx5 in various cellular systems has been well established. In previous studies, we reported that Prx5 reduces LPS-induced microglia activation and protects neuronal cells from neurotoxic substances, such as β-amyloid, iron, diethylhexyl phthalate, and glutamate [ 13 , 18 , 30–34 ]. These findings highlight the necessity of further study on the relationship between the antioxidant effects and intracellular location of Prx5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that glutamate-induced HT22 cell death is by the excessive levels of Ca 2+ [ 27 ]. Thus, we evaluated the effect of 4,6′-anhydrooxysporidinone on levels of Ca 2+ in glutamate-treated HT22 cells using a Fluo-4 AM dye, a membrane permeable fluorescent indicator for Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies suggested that PrP 106-126 increases intracellular calcium levels and calcineurin (CaN) activity in neurons [39,40]. Other researchers have shown that increased calcium levels are associated with the mitochondrial apoptotic pathway in neurodegenerative diseases that involve prions [31,41]. When mitochondrial depolarization occurs with a sustained cytosolic rise in Ca 2+ , the cytosolic phosphatase activity of the serine/threonine phosphatase CaN is activated [42].…”
Section: Introductionmentioning
confidence: 99%